What Does It Take for Research to Be Rehabilitation Research? - Aadal, Lena; Nielsen, Tove Lise; Jensen, Anders Bonde; Bjerrum, Merete; Nielsen, Claus Vinther; Angel, Sanne (Frontiers in Rehabilitation Sciences, 2022)
Six recommendations to facilitate rehabilitation research and supplement existing research practices were identified. Rehabilitation practice requires research addressing different long-term multi-faceted needs and perspectives of end users, including service users, professionals, politicians, and administrators. Research in rehabilitation should therefore integrate different research traditions and methods. Rehabilitation research with a broad focus is sparse, and most of the research takes its starting point in the biomedical research tradition. Through a nominal group process, we developed recommendations to emphasise important issues in rehabilitation research.